ESTIMATION OF GENETIC PARAMETERS AND VARIABILITY IN THE BIVOLTINE SILKWORM BOMBYX MORI L GERMPLASM - LOKESH, G.; MAHESWARI, M.; CHAUDHURI, RITWIKA S.; SEKAR, S.; GOWDA, HALAGUNDE; SREENIVASA, B. T. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Genetic variability is a fundamental and an essential requirement of crop species for the development of superior breeds of high commercial value with strong genetic base. Evaluation and estimation of genetic potentials of silkworm breeds are of prime importance in order to identify promising silkworm genotypes for its commercial exploitation through breeding to enhance the silk productivity for sustainable use. The objective of this study was to evaluate the genetic variability of vast silkworm germplasm and to estimate the genetic parameters of important productive traits. 368 bivoltine silkworm accessions from the germplasm are considered for assessment of genetic variability with five year data on important productive traits. Wide range of variability was observed based on Coefficient of Variation (%) values in the productive parameters viz., fecundity (11.316), weight of the larva (9.285), cocoon yield (7.892), single cocoon weight (8.272 ), shell weight and (12.289) shell ratio (7.082). Based on the multiple trait analysis by Mano index values, 20 top performing accessions were selected and genetic parameters such as heritability, genetic advance and phenotypic & genotypic coefficient of variances were estimated. Pooled ANOVA of 20 selected silkworm accessions indicates significant variations @1% level over the five generations in all the parameters. Higher heritability associated genetic advance was recorded in cocoon weight, shell ratio, shell weight and larval weight, besides, higher genotypic and phenotypic variances in cocoon weight. The results enumerate the importance of evaluation of silkworm germplasm and estimation of genetic parameters for selection of parental stocks for subsequent breeding programme in development of desired breeds.